Hybrid partnerships and social technology at the BoP: a case study - Restelli, Andrea (2016)
Stakeholder expectations have recently led many corporations to engage in initiatives aiming at social development and poverty eradication. However, in spite of the many attempts, compelling results have yet to be produced, leaving the gap between the individuals living at the base of the economic pyramid and those belonging to the higher tiers almost untouched. Some scholars have consequently criticized the lack of contextualization of existing managerial practices pointing their finger to the strong influence of western ideologies, which prevent social initiatives from adapting to the needs of different geopolitical contexts. Through the analysis of a set of Coca-Cola Brazil’s social initiatives (i.e. 'Coletivo Projects') implemented in various Brazilian communities, the present study shows how Coca-Cola Brazil has attempted to produce, in collaboration with local NGOs, an universal kind of 'social technology', which could be easily adapted to different contexts, accelerating the implementation process of social initiatives and increasing their impact.